Foxtail Management in Smooth Brome Hay Meadows - S. R. Lancaster; S. R. Duncan (Kansas Agricultural Experiment Station Research Reports, 2021)
Three different herbicides were applied at early bromegrass greenup and at post hay harvest to assess their effectiveness in controlling foxtail at two producer hay meadow sites in Pottawatomie (PT) and Dickinson (DK) counties. Pendimethalin applied early resulted in the greatest foxtail control, but control did not extend through the season to reduce late-summer infestations. Metsulfuron applied early resulted in approximately 30% visible brome injury. The injury was associated with 77 and 48% brome hay losses when compared to the untreated check, at the PT and DK sites, respectively. Injury from the early spring treatments was exacerbated by six freeze events and cool, dry conditions for three weeks following application. Metsulfuron and pendimethalin applied post-harvest also resulted in visible brome injury, but dry matter yields were not measured. This study will be continued in 2021 without the metsulfuron treatments, but with the addition of sequential pendimethalin treatments.
Keywords: bromegrass; hay; foxtail control; herbicide injury